Selective killing effect of oxytetracycline, propafenone and metamizole on A549 or Hela cells - Shao, Jinhui; Feng, Guihua (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: To determine the selective killing effect of oxytetracycline, propafenone and metamizole on A549 or Hela cells. Methods: Proliferation assay, lactate dehydrogenase (LDH) assay, apoptosis detecting, flow cytometry and western blot were performed. Results: It was found that treatment with propafenone at the concentration of 0.014 g/L or higher for 48 h could induce apoptosis in Hela cells greatly, while it was not observed in oxytetracycline and metamizole at the concentration of 0.20 g/L for 48 h. Oxytetracycline, propafenone and metamizole all displayed evident inhibitory effects on the proliferation of A549 cells. The results of LDH assay demonstrated that the drugs at the test range of concentration did not cause necrosis in the cells. Propafenone could elevate the protein level of P53 effectively (P